Demographic Profile and Outcome of Pediatric Intensive Care Unit - Bastola, Ramchandra; Shrestha, Shree krishna; Sigdel, Bhawana; Poudel, Drishti; Ghimire, Sunita; Ghimire, Amrita; Khadka, Khim Bahadur; Basnet, Anjali (Journal of Nepal Health Research Council, 2023)
Background: Pediatric intensive care provides better observation as well as an intensive treatment, which helps to cure, support, and provide better outcomes for sick children. This study aimed to describe the demographic profile and the outcome of PICU patients, and evaluate the relationship of diagnostic categories with treatment and outcome. Methods: This retrospective cross-sectional study was conducted in a six-bedded PICU from 1 March 2021 to 1 March 2022. Bivariate analysis was used to identify the association between dependent and independent variables. Results: The infants admitted below 6 months of age were 63 (22.3%) and had male predominance accounting for 64%. The main portal of entry of the admitted cases was emergency ward 214(75.6%). Most of the patients 153(54.1%) were admitted for intensive monitoring of their abnormal vitals along with critical care according to our PICU protocol. Respiratory illness 122(43.1%), neurosurgical illness 59(20.8%), and primary infectious disease 52(18.3%) were the common reason for PICU admission. Post-major surgery 2(66.7%), hematological illness 3(37.5%), and cardiac disorders 1(20%) had high mortality rates. Among the portal of admission, the majority of the children (80.0 %) who were admitted to the PICU through the emergency ward died before exiting from the PICU (p<0.0001). Conclusions: Respiratory illness was the most common cause of admission and post-major surgery had the highest mortality rate. Portal of entry was statistically associated with patient characteristics and had a significant relationship with the outcome. Similar studies in other health institutions are required to further analyze the demographic profile and outcome of pediatric critical care in Nepal. Keywords: Infants; Intensive care; Patients; Pediatric